Míra meziškolní mobility žáků základních škol v Česku - Dominik Dvořák; Petr Meyer; Silvie R. Kučerová (Karolinum Press, 2022)
Student transfers between schools or inter-school mobility is an important topic, as it is often associated with other unfavourable conditions for schooling. Repeated transfers may predict an increased likelihood of school failure. On the other hand, school mobility can also serve the school choice. Despite that, data on mobility rate in Czech education have not been available yet. In this study, we use complete set of administrative data on transfers to another school in all Czech basic (comprehensive primary and lower secondary) schools in the consecutive three years (about 150 thousand events). To eliminate structurally enforced transitions, we focused on fully organized schools (grade span of 1-9). The number of departures per year represents on average 3.81% of the number of students. However, there are significant regional differences in the rate of mobility, and we find even greater difference at the level of individual schools. These findings complement the current discussion on inequalities in Czech education and deserve further detailed study.